Harrod's librarians' glossary and reference book : a directory of over 10, 200 terms, organizations, projects and acronyms in the areas of information management, library science, publishing and archive management /: a directory of over 10, 200 terms, organizations, projects and acronyms in the areas of information management, library science, publishing and archive management. (2016) - Prytherch, Ray
No abstract available